Navigating the Financial Landscape: The Importance of Budgeting - Desman Serius Nazara; Linda Ayu Oktoriza; Rahimah Rahimah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study investigates the intricate relationships between income management, expense tracking, budgeting practices, and financial stability among customers of Bank Sumut. Utilizing a quantitative approach with a sample size of 90 respondents, random sampling was employed to gather data. The analysis was conducted using Smart PLS (Partial Least Squares) to examine both direct and indirect effects. The findings revealed the significant influence of effective income management on financial stability, both directly and indirectly through structured budgeting behaviors. While expense tracking was found to be essential, its direct impact on financial stability through budgeting practices was not significant. These results underscore the importance of promoting comprehensive financial management strategies, particularly emphasizing income management and budgeting practices, to enhance financial resilience and well-being. This research contributes valuable insights for financial institutions, policymakers, and individuals, providing guidance for fostering greater financial stability in an ever-evolving economic landscape.